English Bards and Scotch Biography: John Galt's Life of Lord Byron. Issue 1 (June 2016) - Morrison, Robert
Abstract : John Galt's Life of Lord Byron has never fully recovered from the withering criticism that greeted its publication in 1830, but it deserves to be better recognised. It offers some of the finest eye-witness accounts available of Byron in the Levant in 1809—10. It examines a number of striking parallels between Galt's work and Byron's, including Galt's fascination with the Byronic hero. Most intriguingly, it highlights Byron's knowledge and experience of Scotland, and the ways in which he was shaped by its oral traditions, landscapes, history, literature, religion, and language. While more recent biographers have mainly portrayed Byron as unproblematically 'English' or 'British', Galt's Life throws searching light on nineteenth-century constructions of his identity, and establishes the framework for 'considering Byron as a Scottish poet', as T. S. Eliot put it in 1937, more than one hundred years after Galt.